Susceptibilidad antibiótica de enterobacterias aisladas de urocultivos en pacientes atendidos en el Centro de Salud San Juan, Perú – Korea – 2017 - Ríos López, Gloria Vanessa (2024)
The present study aimed to determine the antibiotic susceptibility of Enterobacteriaceae isolated from urine cultures in patients attended at the San Juan Health Center, Peru-Korea - 2017, from 132 urine samples to perform urine culture analysis, the samples were seeded in Mac Conkey Agar and incubated for 24 h. at 37 ° C. Colonies suspected of belonging to the Enterobacteriaceae family underwent a gram staining, and Biochemical tests, such as oxides, Indole, Methyl Red, Voges Proskauer, Citrate, the use of lactose, sucrose and glucose, hydrogen sulfide, for confirmatory identification and the antibiogram technique according to Kirby Bauer for antimicrobial susceptibility . Of the 132 urine culture samples, 72 samples were positive for Enterobacteriaceae and 60 were negative, being Escherichia coli, the enterobacterium with the highest frequency of isolation with 52 (39.00%) of positive samples, in relation to that obtained with Proteus vulgaris 12 ( 9.00%) and Klebsiella spp, 8 (6.00%), likewise, the highest antibiotic resistance of the enterobacteria was with ampicillin with 28 (22.6%) resistant strains, while the highest sensitivity was with the Amikacin with 43 (24.2%) susceptible strains. Concluding, that the most frequently isolated enterobacteria was Escherichia coli and presented the highest antibacterial sensitivity to Amikacin.